Anglų kalbos semantiniai skoliniai Šiaurės Amerikos lietuvių kalboje - Pažūsis, L. (Kalbotyra, 1973)
The present paper presents the first attempt to describe English semantic loans in American Lithuanian. The point of contact which leads to an extension of meaning may be either a phonetic or a semantic similarity or both. The largest number of loan shifts occurred in American Lithuanian between pairs of words which resembled one another both in sound and meaning. Homologous relationship usually involves the so-called international stock of Lithuanian vocabulary, Purely Lithuanian words acquire new meanings usually on the basis of the synonymous extension. Actual collision of meaning, such that we can speak of a semantic confusion, occurred in a number of cases where Lithuanian words were extended to include the usages of English words of partially similar meaning and sound. The similarity of morphemic structure makes this the easy way out for derivatives and compounds.